Borderline Personality Features and Harmful Dysregulated Behavior: The Mediational Effect of Mindfulness - Wupperman, Peggilee; Fickling, Melissa; Klemanski, David H.; Berking, Matthias; Whitman, Jeannie B. (Journal of Clinical Psychology, 2013)
Objectives: The current preliminary study investigated whether deficits in mindfulness (awareness, attentiveness, and acceptance of the present experience) may underlie the relationship of borderline personality disorder (BPD) features to self-injury and overall acts of harmful dysregulated behavior. Method: Nonparametric bootstrapping procedures were used to examine theoretical relationships among variables in a psychiatric sample of adults (N = 70). Participants were asked to imagine themselves in distress-inducing situations and then write what they would actually do to decrease distress in such situations. Results: As hypothesized, mindfulness statistically mediated the relationship of BPD features to reported acts of (a) self-injury and (b) overall harmful dysregulated behaviors. Conclusions: Difficulties in the ability to be aware, attentive, and accepting of ongoing experience may play a role in the relationship of BPD features to harmful dysregulated behaviors. Future research should clarify potential reciprocal effects between BPD features and mindfulness with prospective, multioccasion designs. © 2013 Wiley Periodicals, Inc.
Created from Fastlane, Scopus look-up
Keywords: Borderline personality; Dysregulation; Impulsivity; Mindfulness; Self-injury; Substance